2017
DOI: 10.3389/fnmol.2017.00150
|View full text |Cite
|
Sign up to set email alerts
|

Glial and Neuronal Glutamate Transporters Differ in the Na+ Requirements for Activation of the Substrate-Independent Anion Conductance

Abstract: Excitatory amino acid transporters (EAATs) are secondary active transporters of L-glutamate and L- or D-aspartate. These carriers also mediate a thermodynamically uncoupled anion conductance that is gated by Na+ and substrate binding. The activation of the anion channel by binding of Na+ alone, however, has only been demonstrated for mammalian EAAC1 (EAAT3) and EAAT4. To date, no difference has been observed for the substrate dependence of anion channel gating between the glial, EAAT1 and EAAT2, and the neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Although all three subtypes showed evidence for the anion-conducting K ϩ /Na ϩ co-binding state, K ϩ activated anion current in EAAT-1 and -2 in the absence of Na ϩ but not in EAAC1 (rat homolog of EAAT3). These results suggest subtle differences in the way the anion conductance operates between the subtypes, consistent with results on differences in Na ϩ dependence of the anion conductance (24). These differences may be interesting to explore and may be linked to the different microenvironments of these transporters in their particular location of expression, which varies among the subtypes (22)(23)(24).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Although all three subtypes showed evidence for the anion-conducting K ϩ /Na ϩ co-binding state, K ϩ activated anion current in EAAT-1 and -2 in the absence of Na ϩ but not in EAAC1 (rat homolog of EAAT3). These results suggest subtle differences in the way the anion conductance operates between the subtypes, consistent with results on differences in Na ϩ dependence of the anion conductance (24). These differences may be interesting to explore and may be linked to the different microenvironments of these transporters in their particular location of expression, which varies among the subtypes (22)(23)(24).…”
Section: Discussionsupporting
confidence: 81%
“…However, this simplified model was later revised after it was shown for EAAT4 (30) that the anion conductance can be activated in several other states of the transport cycle, including the inward-facing, K ϩ -bound state that is responsible for K ϩ -induced relocation of the transporter. In addition, Amara and co-workers (24) showed that the glial glutamate transporter subtypes EAAT1 and -2 do not require Na ϩ to acti- Glutamate transporter K ؉ /Na ؉ co-binding state vate the leak anion conductance in contrast to the neuronal subtypes EAAT3 and -4. This finding further supported the idea that the anion conductance is present in many states of the transport cycle, including Na ϩ -free states, and is modulated as the transporter moves through the transport cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, C and D). EAAT2 also mediates large anion current amplitudes under conditions, in which extracellular Na + is completely substituted by K + (36,37). WT and mutant currents displayed similar time, voltage and substrate dependences.…”
Section: L46p Increases Macroscopic Eaat2 Anion Currentsmentioning
confidence: 95%
“…In addition, although glutamate transport results in the import of a net positive charge in both cases, the reversal potential of the current generated by GLAST activity is more negative than GLT-1 and is altered by extracellular chloride concentrations (Wadiche and Kavanaugh, 1998 ). This difference in ion flux is likely due to differences in a secondary property of glutamate transporters—their ability to conduct anions, independent of their transport activity (Wadiche and Kavanaugh, 1998 ; Machtens et al, 2015 ; Divito et al, 2017 ). This property of glutamate transporters is often overlooked by studies examining transporter function in astrocytes, but there is evidence that chloride efflux through glutamate transporter-formed channels greatly influences intracellular chloride concentrations in cerebellar Bergmann glia (Untiet et al, 2017 ).…”
Section: Transportersmentioning
confidence: 99%